A self-critique of facilitating dialogic reflective practice with novice teachers. Issue 5 (2nd September 2020) - Hall, James M.
ABSTRACT: Reflective practice (RP) is known as a cyclical process of identifying issues, discussing how to resolve them, and acting. RP is not supposed to be solitary but rather collaborative between teaching colleagues or supervisors and teachers. Thus, research on teacher development advocates a dialogic approach for mentoring novice teachers in which the participants mutually construct knowledge. The culture of the feedback event, though, can interfere with the participants' intentions for collaborative discussion given the status of the supervisor. In an 18- month ethnographic research project on three first-year teachers, I attempted to engage in dialogic RP with them to identify issues they were experiencing and discuss how to resolve them. In ethnographic research, the researcher is part of the field being studied. Through field notes and interview transcripts, I constructed three critical incidents, or episodes, in which dialogic RP was not attained. Through my recounting of critical incidents with these teachers, I argue that collective understanding of issues and use of the teacher's expertise are important, and that pushing for quick solutions is ill advised. The study shows the subjective side of conducting dialogic RP in a school setting in which participants have different backgrounds and educational perspectives.